Urdu ka guldasta Sooraj mukhi class 7 - Farooqi, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Urdu ke Guldasta: Sooraj Mukhi" is a collection of poems for Class 7 students. The poems explore themes like nature, hope, and human emotions. The title "Sooraj Mukhi" (Sunflower) symbolizes positivity and the pursuit of light, encouraging students to seek wisdom and optimism. The book introduces students to the beauty of Urdu poetry and teaches important life lessons through simple and meaningful verses.
Keywords: Urdu : Textbook; Oxford : Grade 7